A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMPN 1 PANGKALAN KURAS IN READING DESCRIPTIVE TEXTS. - Rossy Damayanti; Effendi Gultom; Rumiri Aruan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This descriptive research is aimed to find out the ability of the second year students of SMPN 1 Pangkalan Kuras in reading descriptive texts. The research data were collected in July 2018. The sample of this research is class VIII H which consists of 33 students. The data were collected by administering a test to the students in the form of multiple choice types. The test contains 25 items. Based on the data analysis, it was found out that the highest score obtained by the students was in comprehending main ideas with the mean score of 79,39 which is categorized into good level. The lowest score was in comprehending factual information with the mean score of 72,72 which is categorized into good level. As a conclusion the ability of the second year students in reading descriptive texts was in good level with the mean score of 75,51.Keywords: The Ability, Reading Ability, Descriptive Texts